تقدير الاحتياجات المائية لري محصولي القمح والشعير مناخياً في محافظة ميسان - السعيدي، علي غليس ناهي (جامعة البصرة - كلية التربية للعلوم الإنسانية, 2012)
لقد تم تقدير الاحتياجات المائية لري محصولي القمح والشعير مناخيا في محافظة ميسان، بالاعتماد على معادلة بليني – كريدل، وأتضح إن الاحتياجات المائية الفعلية قد بلغ "71، 96.6، 112.2، 71، 29.3" ملم لشهور الموسم الزراعي، الممتد من شهر تشرين الثاني ولغاية شهر آذار. كما تبين ان كمية الأمطار الساقطة قليلة لا يمكن الاعتماد عليها في سد الاحتياجات المائية لري المحصولين في أي شهر من شهور الموسم. Has been estimated water requirements for irrigating crops of wheat and barley climate in the province of Maysan, depending on the formula of Pliny - Chridl, and it became clear that the net water needs has reached "71, 96.6, 112.2 0.71, 29.3" mm for the months of the growing season, which extends from November until the month of March. as it turns out that the amount of rainfall a few cannot be relied upon to fill the needs of water for irrigating crops in any month of the season.
Keywords: الموارد المائية; محافظة ميسان; محاصيل الشعير; محاصيل القمح